Collagen implants equipped with 'fish scale'-like nanoreservoirs of growth factors for bone regeneration. (August 2014) - Eap, Sandy; Ferrand, Alice; Schiavi, Jessica; Keller, Laetitia; Kokten, Tunay; Fioretti, Florence; Mainard, Didier; Ladam, Guy; Benkirane-Jessel, Nadia
Implants triggering rapid, robust and durable tissue regeneration are needed to shorten recovery times and decrease risks of postoperative complications for patients. Here, we describe active living collagen implants with highly promising bone regenerative properties. Bioactivity of the implants is obtained through the protective and stabilizing layer-by-layer immobilization of a protein growth factor in association with a polysaccharide (chitosan), within the form of nanocontainers decorating the collagen nanofibers. All components of the implants are US FDA approved. From both in vitro and in vivo evaluations, the sophisticated strategy described here should enhance, at a reduced cost, the safety and efficacy of the therapeutic implants in terms of large bone defects repair compared with current simplistic approaches based on the soaking of the implants with protein growth factor.